PEMANFAATAN MEDIA GAMBAR GUNA MENINGKATKAN KEMAMPUAN SISWA DALAM MENGENAL HURUF HIJAIYAH PADA KELAS 1 DI MIN 5 KABUPATEN BIMA - Zumratun Zumratun (Prodi PAI STIT Sunan Giri Bima, 2022)
This study aims to determine the use of image media to improve students' ability to recognize hijaiyah letters in grade 1 students at MIN 5 Bima Regency and want to know the effectiveness of using image media to improve students' ability to recognize hijaiyah letters in grade 1 students at MIN 5 Bima Regency. This type of research is classroom action research or what we are familiar with (CAR), which is a systematic study of efforts to improve the implementation of educational practice by a group of teachers by taking actions in learning based on their reflections on the results of these actions. The results of this study are first, the use of image media to improve students' ability to recognize hijaiyah letters in grade 1 students at MIN 5 Bima Regency at this pre-cycle stage researchers will see learning to recognize hijaiyah letters directly in class 1 MIN 5 Bima Regency in recognizing letters. hijaiyah in class I has not used the media actively and is still using the lecture method where students are still not actively involved in learning and passive communication tends to occur. Before using the picture media in recognizing hijaiyah letters (Pre-cycle) in grade 1 at MIN 5 Bima Regency, it can be seen that the ability to read hijaiyah letters in the pre-cycle meeting there were 15 children (75%) who were classified as not yet familiar with hijaiyah letters, 5 children ( 25%) quite familiar with the hijaiyah letters. In the implementation of cycle 1 in class 1, the steps in cycle 1 start from planning, implementing, observing and reflecting without using media. At the stage of cycle 1 that the ability to recognize hijaiyah letters in there are 15 children (75%) who are classified as complete, 5 children (25%) who are classified as incomplete. There is a change from before using and after using the hijaiyah letter image media. In the implementation of cycle 2 in grade 1, the steps in cycle 1 start from planning, implementing, observing and reflecting on the media. At the stage of cycle 2 that the ability to recognize hijaiyah letters in there are 20 children (100%) who are classified as complete, 0 children (0%) are classified as incomplete. Second, the effectiveness of using image media to improve students' ability to recognize hijaiyah letters in grade 1 students at MIN 5 Bima Regency. In the pre-cycle stage, the students still do not actively participate in learning and passive communication tends to occur, at the stage of cycle 1 there is a change from before using and after using image media, and at the stage of cycle 2 that the ability to recognize hijaiyah letters with image media can improve the ability to recognize hijaiyah letters in grade 1 students at MIN 5 Bima Regency.